The German bank–growth nexus revisited: savings banks and economic growth in Prussia - SIBYLLE LEHMANN-HASEMEYER; FABIAN WAHL (The Economic History Review, 2021)
This article provides evidence that smaller, regional public financial intermediaries contributed to Germany's industrial development, using a new dataset of the foundation year and location of Prussian savings banks. This extends the bank–growth nexus beyond its traditional focus on large universal banks. Since savings banks were public financial intermediaries, our results further suggest that state intervention can be successful in the financial sector, particularly at the early stages of industrial development when capital requirements are manageable, and access to international capital markets is limited.
Keywords: 330